PENGARUH BIAYA PROMOSI DAN BIAYA PRODUKSI TERHADAP LABA BERSIH YANG DIMEDIASI OLEH VOLUME PENJUALAN (STUDI PADA PT.UNILEVER INDONESIA Tbk PERIODE TAHUN 2015-2019) - Nurul Juwariyah; Rosyati Rosyati (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
PT. Unilever Indonesia Tbk is part of the Unilever group and is one of the largest manufacturing companies in the world in the field of basic goods. Based on preliminary observations, it appears that there is an increase and decrease in net income in the business. Based on these problems, researchers are interested in conducting research on the effect of promotional costs and production costs on profits of PT. Unilever Indonesia Tbk which is mediated by the sales volume for the 2015-2019 Period. This research uses descriptive quantitative method. Sources of data used in this study are secondary data, which consists of data on promotion costs, production costs, sales volume and good profit of PT. Unilever Indonesia Tbk. Period 2015-2019. These data are obtained from financial reports published by PT. Unilever Indonesia Tbk through the website www.idx.co.id. The method used in analyzing the data in this study is descriptive analysis. The data analysis technique in this study used multiple linear regression and path analysis. That is, it is used to predict how the condition, influence and relationship between the independent variable (X) and the dependent variable (Y) are mediated by the variable (Z). Based on the results of the regression analysis that has been carried out, the results are: (1). Promotion cost variables (X1), production costs (X2), and sales volume together (simultaneously) have an effect on net income. (2). Promotion cost variable (X1) has a direct and significant effect on sales volume. (3). The production cost variable (X2) has no direct and significant effect on sales volume. (4). Sales volume cost variable (z) has a direct and significant effect on net income. (5). Promotion cost variable (X1) has no direct and significant effect on net income. (6). The production cost variable (X2) has no direct and significant effect on net income. (7). Promotion cost variable (X1) indirectly through sales volume (Z) has a significant effect on net income. (8). Production cost variable (X2) indirectly through sales volume has no and insignificant effect on net income.